Mechanische Thrombektomie: Akutkomplikationen und Spätfolgen = Mechanical thrombectomy : acute complications and delayed sequelae - Kurre, Wiebke; Bäzner, Hansjörg; Henkes, Hans (Der Radiologe, 2016)
Background Due to the positive evidence for mechanical thrombectomy (mTE), it will be increasingly used in future. Profound knowledge of potential complications, prevention and management of complications is necessary to safely implement mTE into clinical practice. Aim Description of specific complications of mTE and their clinical relevance, measures for prevention and management. Summary of the current knowledge on long-term side effects of mTE. Material and methods Analysis of current trial results and selected case series to address specific topics. Summary of own practical clinical experience. Results Vascular injury (1-5 %) and emboli (5-9 %) are the most relevant intraprocedural complications but the clinical outcome is variable. Measures for prevention and management are described in detail. Vasospasms frequently occur (20-26 %) but rarely need specific treatment and do not affect the clinical course. In the case of restrictive indications the frequency of symptomatic hemorrhage is similar to that for medicinal treatment (up to 8 %). Contrast medium enhancement in the area of the infarction on post-treatment imaging should not be mistaken for hemorrhages. Focal subarachnoid contrast medium enhancement or hemorrhage occurs in up to 24 % of cases and is predominantly benign. In follow-up imaging stenoses or occlusions can be detected in 4-10 % of the treated vessels, most of which are asymptomatic. They are considered to be caused by microtrauma to the vascular wall. Conclusion Clinically relevant complications of mTE are rare. Preventive measures and effective management of complications may even increase safety. Stenoses occasionally occur as a long-term side effect but are asymptomatic in the majority of cases.
Gesehen am 21.10.2019
Online publiziert: 2. Dezember 2015